A Dynamic Model of Firm Entry - Myers, M. G.; Weintraub, E. R. (Review of Economic Studies, 1971)
M. G. Myers, E. R. Weintraub; A Dynamic Model of Firm Entry12, The Review of Economic Studies, Volume 38, Issue 1, 1 January 1971, Pages 127–129, https://d